Nanoreactors stable up to 200 °C: a class of high temperature microemulsions composed solely of ionic liquids. Issue 49 (10th May 2018) - Pei, Yuanchao; Ru, Jie; Yao, Kaisheng; Hao, Lihui; Li, Zhiyong; Wang, Huiyong; Zhu, Xingqi; Wang, Jianji
Abstract : A class of microemulsions solely consisting of ionic liquids was shown to maintain nanoscale droplets up to about 200 °C, and this unique property was used to prepare porous Pt where the microemulsions played the roles of a solvent, a template and a reductant. Abstract : It is a challenge to develop microemulsions which can serve as nanoreactors for the synthesis of nanoparticles and chemical reactions at high temperature. In this work, a class of novel high temperature microemulsions consisting solely of ionic liquids have been designed and prepared for the first time. It is found that nanoscale droplets formed in the ionic liquid microemulsions can be maintained up to 200 °C, and the size distribution of the droplets can be easily tuned by selection of the ionic liquids and varying compositions of the systems. By using such microemulsions as nanoreactors, porous metals such as Pt have been prepared at 180 °C without using any purposely added reductant.